A Case Series of the Use of Piezosurgery Instrument for Minimally Invasive Metopic Suturectomy. Issue 6 (6th February 2021) - McGahan, Ben G; Dhaliwal, Joravar; Pearson, Gregory D; Khansa, Ibrahim; Drapeau, Annie I
Abstract: BACKGROUND: Minimal invasive suturectomy is one of the many surgical approaches to treat isolated single suture craniosynostosis. This approach can be technically challenging in metopic craniosynostosis given the narrow corridor and steep angle of the forehead. New instruments such as the Piezosurgery device (Mectron) have the potential to improve the ability to safely perform minimal invasive surgery in metopic craniosynostosis. OBJECTIVE: To demonstrate the safety and efficacy of Piezosurgery technology in minimal invasive suturectomy for nonsyndromic metopic suture craniosynostosis and to describe our technique. METHODS: A retrospective chart review was performed of all the single metopic suturectomies performed at our single institution from March 2018 to November 2019. Pre-, intra-, and postoperative data were collected to assess the safety of Piezosurgery. RESULTS: The cohort consisted of 12 patients with an average of 95.25 d old and an average weight of 6.2 kg. A total of 91.7% were male, and 91.7% were Caucasian. There were no intraoperative or postoperative Piezosurgery device-related complications in the entire cohort. CONCLUSION: The use of the Piezosurgery instrument was safe in this cohort of minimal invasive metopic suturectomy. This device has greatly increased the ease of this procedure in our hands.